A comparative study of the contact fatigue behavior and associated damage micromechanisms of TiN- and WC:H-coated cold-work tool steel. (August 2015) - Ramírez, G.; Jiménez-Piqué, E.; Mestra, A.; Vilaseca, M.; Casellas, D.; Llanes, L.
Abstract: In this study the contact fatigue behavior of two coated tool steel is compared. They differ in the chemical nature of the coatings as well as on the deposition route used: a conventional TiN coating prepared by cathodic arc technique, and a sputtered WC:H thin film. Both of them have been deposited upon the same wrought tool steel. The mechanical response under cyclic contact loads is assessed by means of spherical indentation. It is found that the WC:H-coated system exhibits an improved contact fatigue behavior with respect to that of the TiN-one, as cohesive and adhesive damage are completely inhibited in the former. Such finding is rationalized on the basis of effective reduction of stresses associated with microasperity contacts. Highlights: Contact fatigue behavior of two coated tool steel samples is compared. TiN and WC:H coatings have been deposited upon the same wrought cold work tool steel. Spherical indentation tests under monotonic and cyclic loading conditions were used. WC:H improved the contact fatigue response of the coated steel with respect to TiN. Low friction and smooth surface of WC:H are pointed out as the improving factors.